Intravitreal aflibercept for diabetic macular oedema: Moorfields' real-world 12-month visual acuity and anatomical outcomes. Issue 3 (May 2020) - Lukic, Marko; Williams, Gwyn; Shalchi, Zaid; Sim, Dawn; Patel, Praveen J; Keane, Pearse A; Hykin, Philip G; Sivaprasad, Sobha; Menon, Deepthy; Bruynseels, Alice; Hamilton, Robin D; Rajendram, Ranjan
Objectives: To assess structural and functional outcomes of treatment with intravitreal aflibercept (Eylea ® ) for diabetic macular oedema in treatment-naive patients. Design: This is a retrospective, real-life, cohort study. Participants and Methods: In all, 92 diabetic patients (102 eyes) receiving intravitreal anti–vascular endothelial growth factor therapy were included. A total of 99 aflibercept-treated eyes were included in the statistical analysis. Each patient had corrected visual acuity in Early Treatment Diabetic Retinopathy Study letters and optical coherence tomography central foveal thickness and macular volume performed at baseline and 12 months. Patients were initiated on a loading phase of five monthly intravitreal aflibercept injections, followed by injections if needed as per clinicians' discretion. Results: The mean number of aflibercept injections received was 6.92. At baseline, the mean visual acuity (standard deviation; Snellen) was 59.7 (16.1) (20/63) Early Treatment Diabetic Retinopathy Study letters, the mean central foveal thickness (standard deviation) was 431 (129) µm, while the mean macular volume (standard deviation) was 9.53 (1.79) mm 3 . At 12 months, the mean visual acuity (standard deviation; Snellen) was 69.6 (15.2; 20/40) Early Treatment Diabetic Retinopathy Study letters (p < .0001). Mean central foveal thickness (standard deviation) was 306 (122) μm (p < .0001) and mean macular volume (standard deviation) was 8.43 (1.58) mm 3 (p < .0001) at 12 months; 33 (33.67%) eyes gained ⩾15 Early Treatment Diabetic Retinopathy Study letters at month 12, and 50 (55.55%) eyes had a decrease in central foveal thickness of ⩾100 µm. Conclusion: There was a significant improvement in visual acuity and in anatomical outcomes in aflibercept-treated eyes at 12 months after commencing treatment for diabetic macular oedema in real-life settings.